Alleviating negative symptoms in schizophrenia using a virtual reality-based therapy targeting social reward learning (ENGAGE): Protocol for a randomised, controlled, assessor-blind pilot study - Valentin M. Donath; Emma Slebsager Ries; Lise Mariegaard; Tina Dam Kristensen; Bjørn H. Ebdrup; Gregory P. Strauss; Patrick M. Fisher; Egill Rostrup; Merete Nordentoft; Rikke Hilker; Marianne Melau; Claudi L. Bockting; et al. (PLoS ONE, 2025)
In individuals with schizophrenia spectrum disorders (SSD), negative symptoms (NS) are known to be associated with low quality of life, predictive of adverse long-term outcomes, and barriers to relevant life goals such as educational, vocational, and social attainment. As social cognition, processes of reward appraisal, and anticipation are impaired in individuals with SSD, these dysfunctions are likely to be intertwined with the pathogenesis of NS. Despite their debilitating nature, there remains a scarcity of treatment options for NS, as they, unlike positive symptoms, are largely unaffected by pharmacological interventions. Among indications that psychosocial interventions can reduce NS, more robust evidence is warranted for interventions that directly target NS. In light of the recent advances in Virtual Reality-assisted psychotherapy (VRT) for the treatment of positive symptoms in schizophrenia (i.e., paranoia and auditory hallucinations), this randomised, assessor-blind, controlled pilot study sets out to test the feasibility and acceptability of a novel VRT aimed at alleviating NS through targeting social reward learning (ClinicalTrials.gov registration ID: NCT06993831). The study will enrol 30 outpatients from the public mental health services of Greater Copenhagen, Denmark, who will be equally randomised to receive either treatment as usual (TAU) or TAU combined with 10 sessions of individual, VR-assisted psychotherapy. Feasibility and acceptability endpoints will be supplemented by clinical interviews and ecological momentary assessments (EMA) for indications of treatment efficacy regarding positive and negative symptomatology, functional outcome, and quality of life. Additionally, neurobiological and behavioural correlates of the intervention will be explored by magnetic resonance imaging (MRI). This study has been registered at ClinicalTrials.gov (NCT06993831).